(untitled) (Journal of the College of Basic Education, 2024)
The importance of research appears in preparing coordination and ability exercises and knowing the effect of these exercises on some biomechanical variables and accuracy of the smashing skill of volleyball players. This skill can be considered a relatively complex skill to perform, and most of the volleyball team players lose their real achievement in performing the skill despite repeated skill training for it. The reason for this is the loss or weakness of consistency in performance of the smashing skill, in addition to weak mechanical ability in the skill. Performance is based on achieving strength and speed at the same time during the performance, whether it is the speed of running close to the skill or the speed of jumping, as well as the speed of the movement of the striking arm leading to the skill, the compatibility of the player’s movement with the moment the ball leaves the prepared player, and the correct and quick timing to hit the ball before it drops to a level lower than the upper edge. For the network, the researcher, through her experience in the field of teaching and training the players of the College of Basic Education volleyball team, decided to develop exercises for compatibility and ability and to know the effect of these exercises on some biomechanical variables (which constitute the ideal skill technique) and accuracy in performing the skill of crushing in volleyball in an attempt From the researcher to develop the actual performance of the players and thus achieve good levels in the Mustansiriya University Championship. The research aimed to prepare coordination and ability exercises, especially for the effectiveness of smashing, and to identify the effect of these exercises on some biomechanical variables and accuracy of the smashing skill for the players of the College of Basic Education volleyball team for the academic year 2023-2024. The researcher assumed that there were statistically significant differences in some of the biomechanical variables and accuracy of the skill. The smash hit in volleyball between the pre- and post-tests for the players of the College of Basic Education volleyball team. The researcher used the experimental method and conducted the pre-tests, then compatibility and ability training was applied, which lasted two months (eight weeks) and at a rate of 16 training units, two training units per week, then the post-tests were conducted. Under the same conditions in which the pre-tests were conducted, the results extracted from the imaging were processed after analyzing them and converting them into statistical numerical values. They were presented in the tables of the fourth chapter and discussed in a scientific manner, supported by relevant scientific sources. The most important conclusions were reached, which is that the exercises using compatibility and ability exercises achieved a positive effect. In the development of some biomechanical variables for the smashing skill. Also, exercises using coordination and ability exercises achieved a positive effect in developing accuracy for the smashing skill. The researcher recommended using coordination and ability exercises in training the smashing skill and applying these exercises to other skills for the game of volleyball and other skills for individual games. It also showed the importance of diversity in using various exercises similar to the actual performance of the skill and according to the motor path of the skill to achieve mechanical variables that achieve accuracy in performance